Evaluating stress distribution in two different designs of class I partial removable dentures - F. Geramipanah; M. Meemarian (Tehran University of Medical Sciences, 1998)
In Present study a digital model of hemimaxillectomy was reconstructed by computer and stress distribution of removable partial dentures in tissues, periodontal ligament and bone were thoroughly evaluated. The maximum stress of two different removable partial denture designs which contained buccal and lingual c-shaped clasps respectively were analyzed and compared. It was assumed that a 90 gram force which is equal to an average obturator's weight is applied outwardly. The results showed that the maximum stress distribution in these two designs is not significantly different.